Draft Second Five Year Plan 1956-1961 Sectorwise Notes With Summaries of Schemes Government of Saurashtra - Planning Commission (Planning Commission, 1955)
The Planning Commission has rightly observed in the First Five Year Plan that “the largest portion of the natural resources of India consists of land and by far the larger portion of its inhabitants are engaged in the exploitation of land. In any scheme of planned economic development of the country, therefore, agricultural reorganisation and reform hold a position of basic importance.
Directorate of Statistics and Planning Government of Saurashtra